Prevalence and risk factors of Vernal Keratoconjunctivitis among a Ghanaian clinical cohort: A case‐control study - Samuel Kyei; Mary Nkansah; Kofi Asiedu; Randy Asiamah; Ebenezer Zaabaar; Ebenezer Afrifa‐Yamoah (Health Science Reports, 2024)
Abstract Background Vernal Keratoconjunctivitis (VKC) has been determined to be highly prevalent in countries within the tropical climate region. However, little evidence from studies conducted within this region has been put forward to support this claim. Aim To determine the prevalence and risk factors of VKC among a Ghanaian clinical cohort. Methods A 3‐year case‐control study was conducted in a tertiary eye care institution, and medical records of patients who had been diagnosed of VKC between 2018 and 2021 were reviewed. Results Medical records of 3800 patients were reviewed. Some 359 cases of VKC were identified, with a population prevalence rate of 9.45 %. Males comprised 57.1 % of the population with VKC, with a male‐to‐female ratio of 1.33 : 1. The disease was more prevalent (40.8%) in children (≤17 years), and the overall odds of incidence decreased by 10% for a unit increase in age. Age and sex‐adjusted models revealed significant positive associations between Keratoconus [aOR = 40.760, 95% CI –5.948 to 339.937], Rhinitis [cOR = 5.183, 95% CI –2.074 to 12.022] and VKC. However, the incidence of VKC was relatively less expressive among pterygium cases [cOR = 0.315, 95% CI –0.077 to 0.846]. Conclusion VKC is highly prevalent among children and is often associated with comorbidities of atopic origin that exacerbate the impact of the disease among this vulnerable population. It is imperative that clinicians provide holistic care for children with VKC.